Praktik Perawatan Masa Nifas Di Kecamatan Pecangaan Kabupaten Jepara Terkait Dengan Faktor Sosial Budaya - Trisna, Adhetia; , Dr. Faizah Betty Rahayuningsih, S.Kep., M.Kes (2016)
Maternal and child health problems is one of the main problems in the health field that is currently happening in the State Indonesia. Every three minutes, somewhere in Indonesia, children under the age of five die. In addition, every hour a woman dies in childbirth or causes related to pregnancy. Both the issue of death and morbidity in the mother and the child actually can not be separated from the socio-cultural factors and the environment in the communities where they are located. The purpose of this study is to investigate the practice of postnatal care in the district of Jepara Pecangaan related to socio-cultural factors. This type of research is quantitative with cross sectional design. Number of samples 54 after the mother postpartum 1-3 days with proportionate stratified random sampling. Instrument research using numbered checklist of 10 items and the questionnaire comprising 60 questions. The results of the study provides an overview of postnatal care about baby care envisaged by 11 (20.4%) mothers provide additional food other than breast milk before the baby is 6 months old, (20.4%), amounting to 51 people (94.4%) gave colostrum to the baby, and 10 people (18.5%) swaddle infants continuously. This description of postnatal care about nutrition, illustrated by 27 people (50%) refrain from certain foods and 28 people (51.9%) consume herbs during childbirth. Activities mothers were 28 people (51.9%) did sit nyandar and as many as 45 people (83.3%) do body massage. Not found mothers who occupied the hot ash and clean the pubic area with a particular herb. Leisure envisaged by most women should always carry objects (scissors, safety pins, nail cutters) if located outside the house or in the house as many as 37 people (68.5%). Society should raise awareness about the importance of knowledge about the practice of postpartum maternal care, while a local health service good for more attention to health and postnatal care practices in the scope of work areas. Keywords: Care, puerperal women, socially and culturally.